2013
DOI: 10.5505/tjtes.2013.37043
|View full text |Cite
|
Sign up to set email alerts
|

De Garengeot's hernia: a case of acute appendicitis in a femoral hernia sac

Abstract: The presence of an appendix vermiformis in a femoral hernia sac is called De Garengeot's hernia. It is a very rare clinical condition and requires emergency surgery. However, preoperative diagnosis of De Garengeot's hernia is difficult. Herein, we report a 58-year-old female who presented with sudden-onset painful swelling in the right groin region. Diagnosis was established based on computed tomography findings, and appendectomy with meshfree hernia repair was performed. The postoperative period was uneventfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 9 publications
1
9
0
Order By: Relevance
“…This is in keeping with the increased incidence of the femoral herniae in women 7. The mean age at presentation is reported as 55 years 5 8. It has been suggested that pregnancy related changes may account for the increased incidence of this condition in women 7.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…This is in keeping with the increased incidence of the femoral herniae in women 7. The mean age at presentation is reported as 55 years 5 8. It has been suggested that pregnancy related changes may account for the increased incidence of this condition in women 7.…”
Section: Discussionsupporting
confidence: 59%
“…The incidence of this is reported in literature between 0.8 and 1% 57. The presence of acute appendicitis within a femoral hernia is even rarer, occurring in 0.08–0.5% of the femoral herniae 68. This finding is termed De Garengeot's hernia 5.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After the year 2000, a total of 32 articles, which presented 34 cases of de Garengeot’s hernia and histology proven appendicitis have been published ( 1, 3, 5 34 ). Thirty-four patients (5 men and 29 women) with a mean age of 71.2 years with this uncommon type of hernia were presented in these studies.…”
Section: Discussionmentioning
confidence: 99%
“…Femoral hernias account for <5% of all hernias and are more common in women with increasing incidence with age,2 and a female to male ratio of 3:1 3. The finding of the appendix within a femoral hernia has a reported incidence of 0.5–5% 4 5.…”
Section: Discussionmentioning
confidence: 99%